Chaos and Truth: B. S. Johnson’s Theoretical and Literary Narratives - Tew, Philip (FOCUS: Papers in English Literary and Cultural Studies, 2000)
From the late 1950s until the posthumous appearance of his last novel in 1975, working-class, London writer B. S. Johnson (1933-73) published poetry and a range of highly experimental novels, stories'and critical essays variously structured around contending motifs of chaos, truth, negation and concepts of facticity. Mid-career an interviewer describes Johnson’s insistence that “All writing is utobiographical, because he believes that one should tell the truth and that the only true knowledge is oneself’ (Depledge 13). The reflexive and biographical elements of his work are self-evident, yet there are subcutaneous theoretical aspects to his work that extend this view of narrative. Yet, despite evidence of this scattered throughout his writings, interpreting his significance and evaluating the more profound qualities of his work appears to have eluded the majority of academics and critics. In the decisive struggle of exegetical commentary, until recently Johnson has been almost erased from the literary-cultural field.